Diabetes care quality indicators improve upon conversion to electronic health records (Health Renaissance, 2013)
Introduction: Electronic medical record (EMR) systems have been touted to improve quality and reduce cost of health care delivery. Objectives: To find out whether electronic health record is better than the paper medical records in recording the quality metrics for management of diabetes. Methods: We tested purported benefits in an academic primary care setting with a pilot of 50 randomly selected subjects with Type 2 diabetes with under continuous care by internists before and after EMR implementation. In comparison to the paper chart period, EMR was associated with better outcomes for glycated hemoglobin (A1C), blood pressure (BP), and smoking cessation counseling documentation using a paired analysis technique.Results: Goal BP (130/80) was achieved for 65% of patients during the paper chart period versus 88% in the EMR period (p = 0.007); mean A1c was 7.60 in the paper chart period versus 7.24 in EMR (p = 0.004); smoking cessation documentation rose from 30% to 84% (p < 0.001) between the paper chart and EMR periods, respectively. Change in mean LDL was not statistically significant (p = 0.636) between the two periods. Conclusion: This pilot study provides a favorable indication that EMR implementation contributes to clinical quality improvement and it also illustrates a feasible applied research method that can be employed by many provider organizations who are called up to conduct continuous quality improvement projects for diabetes care. Health Renaissance, January-April 2013; Vol. 11 No.1; 27-32 DOI: http://dx.doi.org/10.3126/hren.v11i1.7598